Perovskite Films with Reduced Interfacial Strains via a Molecular‐Level Flexible Interlayer for Photovoltaic Application - Zhang, Cong‐Cong; Yuan, Shuai; Lou, Yan‐Hui; Liu, Qing‐Wei; Li, Meng; Okada, Hiroyuki; Wang, Zhao‐Kui (Advanced materials (Weinheim), 2020)
Interface strains and lattice distortion are inevitable issues during perovskite crystallization. Silane as a coupling agent is a popular connector to enhance the compatibility between inorganic and organic materials in semiconductor devices. Herein, a protonated amine silane coupling agent (PASCA‐Br) interlayer between TiO2 and perovskite layers is adopted to directionally grasp both of them by forming the structural component of a lattice unit. The pillowy alkyl ammonium bromide terminals at the upper side of the interlayer provide well‐matched growth sites for the perovskite, leading to mitigated interface strain and ensuing lattice distortion; meanwhile, its superior chemical compatibility presents an ideal effect on healing the under‐coordinated Pb atoms and halogen vacancies of bare perovskite crystals. The PASCA‐Br interlayer also serves as a mechanical buffer layer, inducing less cracked perovskite film when bending. The developed molecular‐level flexible interlayer provides a promising interfacial engineering for perovskite solar cells and their flexible application. A protonated amino silane coupling agent as an interlayer is exploited on rigid and flexible substrates, which not only sets up well‐matched growth underlay but also serves as a structural component of the lattice units, leading to less‐distorted perovskite films, resulting in an obvious advance in device performance, stability, and mechanical tolerance in the corresponding flexible device.